MONEY RECOGNITION AND FAKE CURRENCY DETECTION FOR VISUALLY IMPAIRMENT PEOPLES USING IOT - Selvi A, Arun Santhosh S, Ramkumar M, Sudharasan S, Suganth R (International Journal of Advanced Science and Technology, 2020)
In Modern automation systems currency recognition for real world are required. In modern automation systems they required applications including banknote counting machines, money exchange machines, electronic banking, currency monitoring systems, assist blind persons etc. The recognition of currency is veryimportant for blind people and visually impaired people. Because they are notable to differentbetween the currencies correctly. It is very easy to them to be cheated by the others. One of the most significant issues confronting the outwardly debilitated is the acknowledgment of cash, particularly for paper money. The paper currency has two ways extrinsic as well as intrinsic properties.First the extrinsic properties are not enough to recognize when note is original or fake. In this project, we present the simple computer currency authentication method used in the Indian Bank Note